The effects of a lung recruitment manoeuvre before extubation on pulmonary function after coronary artery bypass surgery - Nel, Stephanus Gerhardus (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScPhysio)--Stellenbosch University, 2013.